Perceived Fit and User Behavior in Activity-Based Work Environments. Issue 1 (January 2022) - Hoendervanger, Jan Gerard; Van Yperen, Nico W.; Mobach, Mark P.; Albers, Casper J.
While activity-based working is gaining popularity worldwide, research shows that workers frequently experience a misfit between the task at hand and their work setting. In the current study, experience sampling data were used to examine how perceived fit in activity-based work environments is related to user behavior (i.e., the use of work settings and setting-switching). We found that workers' perceived fit was higher when they used closed rather than open work settings for individual high-concentration work. Furthermore, more frequent setting-switching was related to higher perceived fit. Unexpectedly, however, this relation was observed only among workers low in activity-switching. These findings indicate that user behavior may indeed be relevant to creating fit in activity-based work environments. To optimize workers' perceived fit, it seems to be particularly important to facilitate and stimulate the use of closed work settings for individual high-concentration work.